The reuse of peanut organic wastes as a growth medium for ornamental plants - A. Mohammadi Torkashvand; M. Alidoust; A. Mahboub Khomami (International Journal of Recycling of Organic Waste in Agriculture)
Background The reuse of organic wastes in agriculture is an appropriate method of environment management. Most plants with ornamental leaves are cultivated in soilless media, in which peat is the basic medium; but the use of peat is questionable due to ecological damage to the environment and economic disadvantages to ornamental plant producers. Peanut shells as remained wastes of cultivating peanut has a considerable volume, compost of which can be used as available sources of ornamental plants medium. A pot experiment was conducted to investigate the possibility of using peanut shell compost in the appropriate bed in the cultivation of ornamental plants. Dracaena marginata was selected as the test plant. The control treatment consisted of a 2:1 ratio of peat to perlite, and peat was replaced by 15, 30, 45, 60 and 100 % v/v of peanut shell compost. The study was done based on a complete randomized design in three repetitions in the ornamental plants and flowers research station, Lahijan, Iran. Results The results showed that the bulk density of the planting beds decreased with the addition of peanut shell compost in comparison to the control. Peanut shell compost increased total nitrogen and available phosphorus and potassium of the media. Peanut shell compost increased plant growth indices, but the growth was reduced in 100 % in the compost treatment. The compost led to increase in nutrient uptake by plants. Conclusion In conclusion, it became known that peanut shell compost is an appropriate alternative to peat as the growth medium of ornamental plants. Because of the favorable properties and high porosity, peanut shell compost can be mixed with low-porosity substrates and applied as a substitute to peat in the cultivation media. It is not suggested to increase peanut compost level by 60 and 100 %.